Pelatihan Pembuatan Marketing Kit Menggunakan Aplikasi Canva untuk Optimalisasi Digital Marketing - Mira Veranita; Ramayani Yusuf; Gunardi (Prapanca : Jurnal Abdimas, 2022)
Digital marketing is currently the most effective approach to improve company marketing. To develop the business and improve marketing, training on making Marketing Kits was conducted using the CANVA application. With the Marketing Kit, digital information about businesses and products can be done more easily, practically and efficiently. Activities are divided into preparation, design and implementation and evaluation stages. The activity was carried out online using Zoom Meeting, for 4.5 hours with a combination of presentation methods, demos and hands-on practice of making logos, business cards, flyers, posters and brochures. The training for the Positive Young Community went smoothly and conducive, all participants were enthusiastic and eager to build their business better. In this all-digital era, in order to be able to compete, business actors including the Positive Young Community need to adapt quickly and be open to various changes and continue to study various opportunities and take advantage of changes. This instantaneous change must still be addressed with the principle of customer focus. This Marketing Kit Training activity is to improve marketing and fulfill customer satisfaction for various information about products and services quickly, creatively and innovatively. Marketing Kit training by utilizing the CANVA application is something new to answer the challenges of changes and developments in digital technology, because consumers no longer have time to read and store business cards, posters, brochures and flyers in physical form (hardfiles), but all now rely on access and storage on smartphones. Despite facing a number of challenges due to online training due to the COVID-19 pandemic, the participants' motivation to participate was maintained.